TINJAUAN AL QUR’AN TERHADAP PERILAKU MANUSIA: DALAM PERSPEKTIF PSIKOLOGI ISLAM - sugeng Sejati (JURNAL ILMIAH SYI'AR, 2017)
Man is God’s most perfect creature on earth. Humans from the beginning exist in a togetherness, he is always in touch with other humans in the container togetherness, friendship, work environment, harmonious citizens and neighborhood, and other forms of social relations. And as a participant togetherness it is certain he gets the influence of his environment, but on the contrary he can influence with his behavior and give a style to the surrounding environment. Humans are equipped among others cipta, rasa, karsa, norm, ideals and conscience as a characteristic of humanity, to him also revealed religion in addition to any relationship with each other, there is also a relationship with the creator. In the Qur’an, humans are repeatedly raised in degree because of the actualization of their souls positively, on the contrary, humans are also degraded for the negative soul actualization. They are crowned far above the heavenly realms, the earth and even the angels, but at the same time, they can be no more significant than the animal creatures. Humans are valued as creatures capable of conquering nature, but they can also degenerate into “the lowest of all low” as well because of their behavior. Therefore, in this condition the emergence of the Qur’an as a source of behavior of human life in carrying out its duties.